Distal middle cerebral artery aneurysms - Endovascular treatment results with literature review - BALTACIOĞLU, FEYYAZ (EDIZIONI CENTAURO, 2002)
Intracranial aneurysms of the distal intracranial arteries are uncommon lesions which are difficult to treat with surgical techniques. Distal middle cerebral artery (MCA) aneurysms constitute approximately 5% of all MCA aneurysms. We report the results of our coil embolization for the treatment of distal MCA aneurysms. Eleven patients (four men and seven women, average age 37 years) with distally located MCA aneurysms were treated. Four of the aneurysms were fusiform in shape and the remainder were saccular. Seven of the aneurysms were in the dominant hemisphere. Four of the seven patients who had saccular aneurysms were treated with selective aneurysm embolization. The remaining seven patients were treated with aneurysmal sac and parent artery coiling. All patients had good retrograde flow into the peripheral branches of the occluded artery. All the procedures were completed successfully without any additional neurological deficits. Coil embolization is a safe and effective technique for the treatment of distal MCA aneurysms. If the parent artery cannot be preserved, pial collaterals can supply adequate blood to prevent neurological deficits.
Keywords: brain aneurysms; endovascular treatment; embolization; GIANT SERPENTINE ANEURYSMS; GUGLIELMI DETACHABLE COILS; INTRACRANIAL ANEURYSMS; VERTEBRAL ARTERIES; PARENT ARTERY; OCCLUSION; MANAGEMENT; CIRCULATION; FEATURES